Do Low Vegetables and Fruits Intake Contribute to Overweight Status of Healthy Reproductive Age of Malay Women in Selangor? - Abu Baharin, Mohamed Fakhri; Isa, Zaleha Md.; Ismail, Noor Hassim; Ja'afar, Mohd Hasni; Tamil, Azmi Mohd; Yusof, Khairul Hazdi (Pakistan Journal of Nutrition, 2015)
Overweight and obesity posed major risk factors for a number of chronic diseases, including diabetes, cardiovascular diseases and cancer. Prevalence of overweight and obesity among adults especially women show an increasing trend. The aim of this study was to determine the prevalence of overweight among healthy reproductive age of Malay women in Selangor and to determine whether low vegetables and fruits intake contribute to overweight among them. A cross-sectional study was conducted among adult women in selected urban and rural areas in Selangor. Simple random sampling was used in selecting participants. Inclusion criteria for the participants are Malay, within reproductive age (15-45 years old) and healthy (without any chronic diseases). Data were collected using a questionnaire-guided interview. A total of 630 respondents were recruited in this study. The respondent’s mean age was 39.6±3.697 years old. The prevalence of overweight among the respondents was 61.0%; in which 37.8% were categorized as pre-obese and 23.2% were obese. Prevalence of overweight was higher in those above 40 years old, had lower education level, unemployed, married, having children, ever breast-feed, not using contraceptive and having low intake of vegetables and fruits. There was a significant association between marital status and overweight with OR 2.88 (CI 1.56-5.31; p = 0.001). As a conclusion, the prevalence of overweight in this study was high particularly among married women. Low vegetables and fruits intake did not contribute to the overweight status of healthy reproductive age of Malay women in this study.